Solução Analítica de Suporte à Decisão no âmbito da Gestão Académica no Ensino Superior - Sérgio Manuel Soares Esteves (2016)
In a highly competitive market,access to information is increasingly becoming one of the main differentiating factors. In addition to human resources, information is considered to be any organisations' most important asset. Due to the high amount of information available, analysing and drawing important business conclusions in the least time possible has become an imperative. Entreprise Resource Planning systems, as well as other business support systems, are the greatest source of information and support to daily operations. The information contained in these systems can accelerate decision-making, if analysed as properly and as quickly as possible. New technological solutions have risen, as a complement to the already existing systems, and also, in some way, as a contribute to a more substantial return to organisations. These systems are knowb as Business Intelligence and, along with helping in the decision-making process,as mentioned above, they were created as a support tool to transform information that was not until now accessible on time. The larger the organisation and the greater the number of systems used in daily operations, the more advantageous it becomes to the firm. In this context, many firms begin to feel the need to accelerate their decision-making process, by introducing these systems in the working place. This project seeks to answer to the needs of control and decision-making in the field of Academic Management, with the aim of being implemented in the future in universities and polytechnic institutes. Through the analysis of demand and effectiveness and through the control of revenue,attendance and planning an answer is given to the needs and requests in this field. To conclude, the objective of this dissertation will be to describe a functional and technical methodology to the creation of a Business Intelligence solution, from the creation of a Data Mart, ETL processes, Metadata and even reporting tools. The field of Business Intelligence has been going through a major evolution over the last years and, as a result thereof, during the investigation of the information using the reporting tool. The solution will be subject to analysis as a way to find alternatives to investigate information (reporting tools) that are not currently being used. Finally, after analysing the results and the tools that were used, a path is suggested, with the analysis of its impact in the final solution together with the newly explored technologies being explored in more detail.